2022
DOI: 10.1038/s41420-022-00869-x
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine inhibits TNF-α-induced cecal damage by enhancing RIP1 ubiquitination to attenuate lethal SIRS

Abstract: Systemic inflammatory response syndrome (SIRS) is a sepsis-associated inflammatory state and a self-defense mechanism against specific and nonspecific stimuli. Ketamine influences many key processes that are altered during sepsis. However, the underlying mechanisms remain incompletely understood. In this study, TNF-α-treated mice, as well as HT-29 and L929 cell models, were applied to characterize TNF-α-induced systemic and local cecal tissue inflammatory responses. Behavioral, biochemical, histological, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…Cecum plays a critical role during the SIRS process. Our previous study has detected severe damage and necroptosis that occurred in the cecum of TNF-induced SIRS mice 9 . More speci cally, consolidated evidence has also suggested that cecum damage increased circulating HMGB1 levels and elevated in ammatory cytokines released by over-activated microglia and led to a neurological disorder, thereafter 39,40 .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Cecum plays a critical role during the SIRS process. Our previous study has detected severe damage and necroptosis that occurred in the cecum of TNF-induced SIRS mice 9 . More speci cally, consolidated evidence has also suggested that cecum damage increased circulating HMGB1 levels and elevated in ammatory cytokines released by over-activated microglia and led to a neurological disorder, thereafter 39,40 .…”
Section: Discussionmentioning
confidence: 90%
“…Although ketamine inhibits HMGB1 production via multiple mechanism 7 , our previous work had represented the protective effect of ketamine on the neuron, L929 cell, and cecal epithelial cell by inhibiting phosphorylation of MLKL, restricting necroptosis 8,9 . However, a few research focus on the role of ketamine in the neurovascular unit like BBB.…”
Section: Introductionmentioning
confidence: 99%
“…However, it remains concerning that despite alleviating offspring behaviour, uoxetine still crosses the placenta and acts directly on the foetal brain during vulnerable developmental periods with unpredictable echo effects that may not manifest until adolescence or adulthood (Houwing et al 2019). Ketamine, in contrast, has not been shown to accumulate in foetal tissue or breastmilk, conferring an advantage (Deng et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to caspase‐dependent programmed cell death, necroptosis is an unprogrammed and autonomous form of cell death that can be activated by various virulence factors discharged by the pathogen. However, sepsis‐induced changes in organ perfusion and hypovolemia can also contribute to necrosis 178 . This process, in turn, can bolster the release of extracellular “alarm proteins” such as HMGB1, thereby exacerbating local inflammation.…”
Section: Regulatory Mechanisms Involved In Sepsismentioning
confidence: 99%